Factors reputation of modern Russian high school and their influence on the formation of values of students - M. S. Sokolova; M. A. Yefimova (Путеводитель предпринимателя, 2020)
The article examines the factors shaping the reputation of a modern Russian university and their relationship with the formation of valuable orientations of students.